Based on the Network Pharmacology to Investigate the Mechanism of Qingjie Fuzheng Granules against Colorectal Cancer. (4th March 2022) - Fang, Yi; Yang, Chi; Lu, Yao; Wei, Lihui; Zhao, Jinyan; Lu, Lisha; Lin, Jiumao
Abstract : Qingjie Fuzheng granules (QFG) exert an anticancer effect against colorectal cancers (CRC). However, the pharmacological molecular mechanisms are still unclear. This study was aimed to establish a simple method to predict targets of QFG against CRC by the network pharmacology strategy. 461 compounds and 1559 targets in QFG were enriched by BATMAN-TCM. 21 of the common targets were obtained by the groups of "Jun, " "Chen, " "Zuo, " and "Shi" medicine in QFG. The enrichment analyses of GO functional terms, KEGG pathway, and OMIM/TTD diseases displayed the targets in the different and complementary effects of four functional medicines in QFG. Then, 613 differential targets for QFG in CRC were identified. GO functional terms and KEGG pathway analyses showed that QFG regulated the inflammatory function and lipid metabolic process. There were also targets that played a role in the binding to the receptors in membranes, in the activation of the transportation signal, and provided pain relief by regulation of the neural related pathways. Next, the protein-protein interaction network was analyzed, and the levels of the predicted targets in CRC primary tumor were explored, and 7 candidate targets of QFG against CRC were obtained. Furthermore, with real-time PCR and enzyme-linked immunosorbent assay (ELISA) analysis, downregulation of dopamine D2 receptor (DRD2) and interleukin-6 (IL-6), and upregulation of interleukin-10 (IL-10) were identified following the treatment of QFG. At last, the survival and prognosis of the potential targets of QFG in CRC patients were analyzed by GenomicScape, and IL-6 was suggested to be an index for the regulation of QFG in CRC. These results might elucidate the possible antitumor mechanism of QFG and highlight the candidate therapeutic targets and the application direction in clinical treatment for QFG.